An 8-week ketogenic diet improves exercise endurance and liver antioxidant capacity after weight loss in obese mice - Wang, Ying; Dong, Yunlong; Zhang, Ying; Yan, Jiabao; Ren, Cuiru; Ma, Hong; Cui, Zhenwei (Frontiers in Nutrition, 2023)
Evolving evidence supports the role of the ketogenic diet (KD) in weight loss. However, no coherent conclusions are drawn on its impact on the effect of KD on exercise and antioxidant capacity after weight loss in obese individuals. We evaluated the exercise performance, energy metabolism and antioxidant capacity of mice after weight loss using high-fat diet-induced obese mice, and used KD and normal diet (ND) intervention, respectively, to provide a theoretical basis for further study of the health effects of KD. Our results showed that the 8-week KD significantly reduced the body weight of obese mice and improved the performance of treadmill exercise, but had no significant effect on grip strength. Serum biochemical results suggest that KD has the risk of elevating blood lipid. In liver tissue, KD significantly reduced the level of oxidative stress and increased the antioxidant capacity of the liver. Our findings suggest that the intervention with KD led to weight loss, modulate energy metabolism and improve aerobic exercise endurance in obese mice. Despite its antioxidant potential in the liver, the utilization of KD still requires caution. This study underscores the need for further investigation into the health impacts of KD, especially in regard to its potential risks.